Exploring value-landscape associations in the Tanzanian Southern Highlands - Arki, Vesa (fi=Turun yliopisto|en=University of Turku|, 2018)
Many decisions in land use management are made without sufficient local knowledge. The ecosystem service framework has brought attention to the relationships between humans and nature by conceptualizing how ecosystem functions are identified as different benefits for local communities. Through place-based participation locations of landscape benefits are mapped. These locations can be combined with the underlying physical landscape structures to define value-landscape associations that help to understand how ecosystem functions are turned to human benefits in different socio-ecological contexts. In this thesis I studied value-landscape associations in Iboya, Lulanzi and Tungamalenga villages in the Tanzanian Southern Highlands. Information on the landscape values of the communities was collected in a participatory mapping campaign and further spatially analyzed to map spatial distribution. I collected information on the landscape structure via visual interpretation methods and calculated landscape indices to describe the physical village landscapes. Based on the available data I calculated statistical analyses to define value-landscape associations. The physical landscapes in Iboya and Lulanzi are characterized by heterogeneity while in Tungamalenga the landscape is more homogenous. In all villages landscape heterogeneity tended to be higher near the settlements. The trends in value distribution are similar between villages as cultural values are concentrated at the settlement areas and provisioning values show a more scattered pattern in the landscape. Important areas of value co-existence were identified at central settlements and certain forested areas. The general value-landscape associations in all the villages are very practical as for example wild food is collected from forested areas. The value-landscape associations indicated that growth in landscape heterogeneity results in higher value richness and diversity in Iboya and Tungamalenga while in Lulanzi the relationship is not as strong. The study highlights that the realization of value-landscape associations are sensitive to the local scale practices and the wider socio-ecological context. Therefore, the created information can be useful for the local-scale land use management in the villages.